The Impact of Policy Changes in the Distribution of Subsidized Fertilizers and the Use of Biopesticides on Chili Crop Productivity in Rejang Lebong Regency, Bengkulu Province - Gabrienda, Gracia; Yanuarti, Mira; Prisdinawati, Dwita; Arianto, David; Saputra, Jepri (West Science Interdisciplinary Studies, 2025)
This study examines the impact of changes in subsidized fertilizer distribution policies and the use of biopesticides on the productivity of chili plants in Rejang Lebong Regency, Bengkulu Province. A quantitative approach was employed, utilizing a sample of 85 chili farmers. Data were collected through a Likert-scale questionnaire (1-5) and analyzed using SPSS version 25. The results revealed that both subsidized fertilizer policies and biopesticide usage significantly and positively influenced chili productivity, explaining 53% of the productivity variance. Descriptive statistics indicated moderate to high levels of satisfaction with fertilizer policies and biopesticide effectiveness. These findings emphasize the importance of integrated policy measures to enhance agricultural productivity and sustainability. Recommendations include improving fertilizer distribution systems and promoting biopesticide awareness among farmers.